Tantangan Mahkamah Pidana Internasional (ICC) dalam Pengusutan Kejahatan Serius pada Perang Rusia-Ukraina - Ashri, Abdul Munif (Jurist-Diction, 2025)
This study aims to identify the challenges the International Criminal Court (ICC) may face in prosecuting the serious crimes committed during the Russia-Ukraine War. The research employs a normative legal method with statutory and conceptual approaches. The results show two substantial ICC challenges: the immunity of the alleged person as the Russian Head of State; and the issue of legitimacy regarding impartiality. Since Russia is not a State Party to the Rome Statute, the ICC’s jurisdiction over the Russia-Ukraine War was not invoked through the UN Security Council referral mechanism but rather through Ukraine’s approval or acceptance. Furthermore, the ICC’s legitimacy as an impartial judicial body will be at stake if there is a tendency for one-sided prosecution that only focuses on the Russian forces. When allegations of comparable serious crimes perpetrated by Ukrainian forces are ignored, and the Ukrainian criminal justice system does not work effectively to prosecute the alleged perpetrators, the ICC could be considered practicing ‘group-based selectivity’. Thus, the practice of selectivity can undermine the legitimacy of the ICC.